Multiplex CRISPR/Cas9-mediated editing of seven glycosyltransferase homologs in Nicotiana benthamiana to produce stable, Cas9-free, glycoengineered plants - Kaur, Chetan; Song, Hayoung; Lee, Myungjin; Kim, Seo-Young; Seo, Dong-Hoon; Kang, Hyangju; Sohn, Eun-Ju; Ran, Yidong; Koo, Okjae; Lee, Geung-Joo (Frontiers in Plant Science, 2025)
IntroductionPlant-based systems hold great potential for producing therapeutic proteins, but differences in N-glycosylation pathways between plants and mammals present major technical and regulatory barriers. In particular, plant-specific α-1,3-fucosylation and β-1,2-xylosylation can generate immunogenic glycan structures, necessitating genome engineering to humanize plant glycosylation profiles.MethodsWe applied multiplex CRISPR/Cas9 genome editing in Nicotiana benthamiana to simultaneously target five α-1,3-fucosyltransferase genes and two β-1,2-xylosyltransferase genes. Resulting T0 transformants were genotyped to assess mutagenesis, and subsequent T1 and T2 generations were screened to identify Cas9-free, homozygous plants. Growth and morphological characteristics were evaluated across germination, flowering, and seed production stages.ResultsTwo T0 lines (HL40 and HL64) exhibited successful edits in all seven target genes, with mutations consisting of single-base insertions and deletions up to 26 bp. In later generations, we identified stable Cas9-free homozygous lines containing mutations across all targeted loci. Three T1 transformants with the highest number of homozygous alleles were selected to generate T2 progeny. Heterozygous alleles segregated into homozygous genotypes in the T2 generation, accompanied by confirmed loss of enzymatic activity. T2 plants showed no detectable morphological or growth differences compared with wild-type plants, indicating no adverse phenotypic effects. Ultimately, we generated 12 independent Cas9-free, glycoengineered, homozygous lines.DiscussionThis work establishes the first N. benthamiana lines that are fully Cas9-free and homozygously edited at all seven key glycosyltransferase loci. These glycoengineered lines provide a stable and versatile genetic platform for future plant-based glycoengineering efforts and the production of recombinant therapeutic proteins.